THE EFFECT OF "THE FASHION OF THE GENES EDUCATIONAL EVENT" ON THE GIFTED STUDENTS’ POSITIVE ATTITUDE CHANGE ON FASHION AND SUSTAINABILITY - ÇAKMAK, Şükran; ÖZ, Cantürk; ÇEĞİNDİR, Neşe Yaşar (SSD Journal, 2022)
This study aims to reveal the importance of fashion awareness education on sustainable fashion design for gifted students and the change in their attitude and behavior. In addition, by teaching the attitudes and behaviors of sustainable fashion design; attention is drawn to the importance of applied (practical) training. The research was carried out at the Mamak Science and Art Center within the scope of the TÜBİTAK 4004 Nature and Science Schools “Modelling Agricultural Gene Resources with Technology” project. The study sample consists of 30 gifted students aged between 12-17 who voluntarily participated in this study. The quasi-experimental design approach was used with preand post-tests. In the study, named “the Fashion of Genes” theoretical knowledge training was applied with slide presentations and a collage workshop using natural materials. Statistical analyzes of the data were made with the Wilcoxon Ordinal Numbers Test by the SPSS program.After the training, it was observed that there was a significant difference (p=,000) in the sum of the student’s attitude and behavior scores towards fashion awareness, and 50% of them planned to use their clothes for more than 2-3 years. It was concluded that the training on "the need to think about whether there is a reason (need) before purchasing the product" has a significant (p=,020) effect on increasing awareness. When the sums of general attitude and behavior scores in the subjects of "Fashion and Sustainability" (p=,013), "Fashion Ethics" (p=,003), and "Fashion Trends" (p=,002) are compared, it was found to be a significant change (p=,000). As a result, it was concluded that sustainable fashion design education affects the attitude and behavior change of gifted students. In addition, with sustainable fashion design education, awareness was created for students to think multi-dimensionally in future projects. Thus, an important step was taken to support the circular economy